Taxonomic Studies on the Daedaloid and Hexagonoid Polypores Form the Forest of Western Maharasta - Rathod, Mulchand M. (Recent Research in Science and Technology, 2011)
For the present investigation the polypore fungi from the forests of Western Maharashtra were studied. Polypores are the wood rotting fungi that attack wood and play a major role in the processes of its decay. Two kinds of wood decay are distinguished the white rot and the brown rot. The collections were made from twelve different sites and sixty five specimens were critically examined with respect to their macro and micro morphological characters of the basidiocarp, cultural behaviour and enzyme tests. On the basis of these observations four genera, namely Daedalea Fr., Daedaleopsis Schroetl., Lenzites Fr. and Scenidium (Klotzsch.) O. Kuntz. and fifteen species namely, Daedalea africana, Daedalea quercina, Daedaleopsis nipponica, Daedaleopsis sibirica, Daedaleopsis confragosa, Daedaleopsis flavida, Lenzites acuta, Lenzites adusta, Lenzites vespacea, Lenzites karnalensis, Lenzites vernieri, Scinidium capillaceum, Scinidium apiarium, Scinidium niam-niamensis, Scinidium tenuis are separated. Out of these fifteen species of wood rotting polypores only two species Daedalea africana and Daedalea quercina are causing white rot and remaining thirteen species causes brown rot.